2023
DOI: 10.1002/aisy.202200339
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Actuation of Magnetic Soft Robots Using Deep Reinforcement Learning

Abstract: Magnetic soft robots (MSRs) have attracted growing interest due to their unique advantages in untethered actuation and excellent controllability. However, actuation strategies of these robots have long been designed out of heuristics. Herein, it is aimed to develop an intelligent method to solve the inverse problem of finding workable magnetic fields for the actuation of strip‐like soft robots entirely based on deep reinforcement learning algorithms. Magnetic torques and a dissipation force to the Cosserat rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…Recently, Yao et al [356] have used RL algorithms for an intelligent approach that tackled the inverse problem of discovering feasible magnetic fields for actuating strip-like soft robots. By employing a helical magnetic hydrogel microrobot, controlled through RL algorithms, the study by Behrens and Ruder [361] demonstrated the capability of the robot to autonomously navigate complex environments.…”
Section: Reinforcement Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yao et al [356] have used RL algorithms for an intelligent approach that tackled the inverse problem of discovering feasible magnetic fields for actuating strip-like soft robots. By employing a helical magnetic hydrogel microrobot, controlled through RL algorithms, the study by Behrens and Ruder [361] demonstrated the capability of the robot to autonomously navigate complex environments.…”
Section: Reinforcement Learning Modelsmentioning
confidence: 99%
“…Beyond these components, the system involves simulations to demonstrate the design's functionality and performance under various conditions. Reproduced from [356]. CC BY 4.0.…”
Section: Figurementioning
confidence: 99%
“…The model is further implemented using the lattice Boltzmann method [50] to simulate fluid-structure interactions, such as a swimming magnetic soft robot. Reduced models of slender hard-magnetic structures, such as shells and plates [51][52][53] as well as rods, [54][55][56][57][58][59] have been developed to further reduce the computational cost. They are very efficient and thus promising for real-time simulations and inverse design of robots.…”
Section: Introductionmentioning
confidence: 99%
“…They are very efficient and thus promising for real-time simulations and inverse design of robots. [57,59] Another challenge is the nonlinear interactions at the interface between the soft robots and their environments, such as friction and adhesion. In many soft robotic systems, [37,[60][61][62][63][64][65][66][67][68] friction and adhesion play a critical role in locomotion performances, especially for those robots that can climb walls, hang from ceilings, and run on granular surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It requires no prior knowledge and derives optimal policies through trial-and-error interactions with the environment. [13,14] As such, DRL has seen widespread use in novel controller design. [15,16] Bellegarda et al developed a DRL-based approach enabling robust jumping on uneven terrain.…”
Section: Introductionmentioning
confidence: 99%